PELAKSANAAN BUDIDAYA AYAM PETELUR SEBAGAI BENTUK ASIMILASI BAGI NARAPIDANA - Mahanta Dwi Sepdiharja (Universitas Halu Oleo, 2020)
The research is about how to apply a program of cultivation breeder of chicken as to realization of assimilation for prisoner in prison of class IIB in Tuban City. The research use a survey method that to have a character of description is describe that is to will explain about to aspect how to applying of cultivation breeder of chicken in the prison, and then to will be doing take analysis and take to a conclusion with the using method approach qualitative. The result was to research can be based it will be did doing in the prison of class IIB in Tuban city about how to applying a program breeder of chicken for the prisoner it will be to indicate a result that good enough for going to social of reintegration of prisoner with a hope it can be will some give to good skill about the breeder of chicken for the prisoner, so it is able making grow to the spirit of entrepreneur, if they were left from prison. But, in reality in a prison, it will be can found some problem, that is 1. Less Cooperation with the various of stakeholder to related for to supported this research, 2. Less information about this program by the prison of employee to stakeholder that related about reach for a good result.